2019
DOI: 10.1111/ceo.13454
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal choroidal flow on optical coherence tomography angiography in central serous chorioretinopathy

Abstract: Importance Analysing choroidal flow in central serous chorioretinopathy (CSC) with novel device. Background To examine the abnormal morphology of choriocapillary flow with optical coherence tomography angiography (OCTA) according to the presence of subretinal fluid (SRF) in CSC. Design A hospital‐based retrospective study. Participants We analysed OCTA results of 68 eyes (68 patients) diagnosed as CSC with or without SRF (active and resolved CSC, respectively) at the Asan Medical Center. Methods We classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Moreover, the definitive diagnosis of CNV in CSC using dye-based angiography may be challenging due to overlap in clinical presentations and image findings. e advent of OCTA has enabled visualization of choriocapillaris and other vascular signal abnormalities at the choriocapillary level in CSC patients [11]. As in the previous study, we analyzed OCTA findings to detect CNV and divided patients into two groups (with or without CNV).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the definitive diagnosis of CNV in CSC using dye-based angiography may be challenging due to overlap in clinical presentations and image findings. e advent of OCTA has enabled visualization of choriocapillaris and other vascular signal abnormalities at the choriocapillary level in CSC patients [11]. As in the previous study, we analyzed OCTA findings to detect CNV and divided patients into two groups (with or without CNV).…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary study, only age had a significant correlation with the DCP vascular density of CSC among the variables, including duration of macular detachment, refractive errors, SRF height and anti-vascular endothelial growth factor (VEGF) use, which were previously reported to be related to choroidal changes in CSC 17 , 18 . Therefore, comparing the results of CSC and RRD, age-matched groups were selected (42 eyes with CSC and 26 eyes with macula-off RRD) and analyzed to minimize age-related confounding factors.…”
Section: Methodsmentioning
confidence: 88%
“…Considering the association of choroidal hyperpermeability and choroidal thickness, IVB may reduce choroidal hyperpermeability followed by a subsequent reduction in the choroidal thickness [ 16 ]. Abnormal choroidal flow as seen on OCT angiography is associated with CSC disease activity [ 21 ]. Our study demonstrated a significant reduction of SFCT and CRT following IVB, especially in the eyes with resolved CSC.…”
Section: Discussionmentioning
confidence: 99%